Factors affecting green innovation among convection industry employees in West Jakarta - Rani Herliyani; Netania Emilisa; Viona Kayla; Amanda Cantika Putri Efendhi; Marsha Anita Muhadi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to identify the factors that drive the emergence of green innovation among employees working in convection businesses located in West Jakarta. A quantitative descriptive approach was employed through the distribution of questionnaires to 100 respondents selected using a purposive sampling method. The findings reveal that several internal and external company elements contribute to enhancing environmentally friendly practices, such as the efficient use of raw materials, the development of sustainable products, and the firm’s ability to respond to environmentally conscious market demands. Nonetheless, not all organizational aspects were found to exert a significant influence, indicating that green innovation efforts still require stronger support, particularly in terms of leadership. This study is limited to a specific region and industrial characteristics, and therefore future research is recommended to expand the research context and incorporate additional factors to achieve a more comprehensive understanding. Keywords: Green Human Capital; Green Structural Capital; Green Relational Capital; Green Transformational Leadership; Green Innovation